Causes and implications of emergency conversion on on-pump during coronary artery bypass grafting in patients with ischemic heart disease - A. V. Rudenko; O. O. Zhurba (Ukrainian Journal of Cardiovascular Surgery, 2018)
Emergency conversion on-pump during OPCABG significantly impairs the immediate results of myocardial revascularization.The purpose of this study was to review the causes and consequences of these cases based on the results of a retrospective analysis of 4,668 patients. It was established that in patients with the use of on-pump surgery, there is a significant increase of the frequency of all postoperative complications, and in case of emergency conversion postoperative lethality is increasing too. The reasons for emergency conversion were hemodynamic instability, elevation of the ST segment, and rhythm disturbances. These intraoperative complications were manifested in other patients, but they were eliminated without the use of on-pump surgery. We believe that the complications during the operation have similar provocative factors that should be taken into account when determining the predictors of their development.